The Grand Duchy of Berg in the Napoleonic Wars in the field diary of Lieutenant Zimmermann - K. A. Ispanov (Гуманитарные и юридические исследования)
Introduction. After becoming emperor of France in 1804, Napoleon Bonaparte had to solve an extremely difficult geopolitical situation: the old European monarchies were in no hurry to recognize the legitimacy of the newly-made emperor’s power, so France had to act not only by force of arms, but also by demonstrating the effectiveness of the new order by creating model states located in Germany and becoming a showcase. One of these model states was the Grand Duchy of Berg, formed on the territory of the former duchies of Cleves and Berg in 1806. Napoleon sends his officials to the young duchy, actively carries out reforms for the development of the economy, the social sphere, as well as reforms of the army.Materials and methods. Newly formed military contingents recruited on the territory of the states were to take part in the conflicts of the first quarter of the XIX century, and the Grand Duchy of Berg was no exception.Analysis. The article considers the reflection of the participation of the Berg infantry in the Napoleonic Wars from 1807 to 1814 on the pages of the field diary of sergeant and then lieutenant of the 1st Infantry Regiment of the Grand Duchy of Berg P. Zimmermann. Attention is focused on the perception of Spaniards and Russians by German soldiers, on the image of the war as a whole based on the diary mentioned above. The images drawn by Zimmermann are ambivalent at first: he pays tribute to the courage, perseverance and patriotism of the Guerilliers, complains about cruelty and excesses, condemns looting by soldiers of allied units.Result. The tragic fate of the Berg contingent in Russia leads the author of the diary to speculate about good and evil, about combat brotherhood, about the senselessness of losses, the brutality of the Cossacks, the ingratitude of German civil officials. But the leitmotif of the whole narrative is the glorification of the honor of Berg’s soldiers and officers, who did not lose their dignity in the most dangerous and difficult situations.